Phrawisaithat khō̜ng Phrabāt Somdet Phračhō̜mklao Čhaoyūhūa tō̜ khwāmplīanplǣng sangkhom Thai - Narưmon Thīrawat (Samnak Sinlapa læ Watthanatham, Mahāwitthayālai Rātchaphat Nakhō̜n Sawan, 2008)
Biography of King Rama IV of Thailand.